Eight-Hour Continuous Normothermic Ex Vivo Kidney Perfusion Is a Safe Preservation Technique for Kidney Transplantation: A New Opportunity for the Storage, Assessment, and Repair of Kidney Grafts. Issue 9 (September 2016) - Kaths, J. Moritz; Echeverri, Juan; Goldaracena, Nicolas; Louis, Kristine S.; Chun, Yi-Min; Linares, Ivan; Wiebe, Aryn; Foltys, Daniel B.; Yip, Paul M.; John, Rohan; Mucsi, Istvan; Ghanekar, Anand; et al.
Abstract : Background: Hypothermic kidney storage causes preservation injury and is poorly tolerated by renal grafts. We investigated whether static cold storage (SCS) can be safely replaced with a novel technique of pressure-controlled normothermic ex vivo kidney perfusion (NEVKP) in heart-beating donor kidney transplantation. Methods: Right kidneys were removed from 30 kg Yorkshire pigs in a model of heart-beating donation and either preserved in cold histidine-tryptophan-ketoglutarate solution for 8 hours (n = 5), or subjected to 8 hours of pressure-controlled NEVKP (n = 5) followed by renal heterotopic autotransplantation. Results: During NEVKP, physiologic perfusion conditions were maintained with low intrarenal resistance and normal electrolyte and pH parameters. Aspartate aminotransferase and lactate dehydrogenase as injury markers were below the detectable analyzer range (<4 and <100 U/L, respectively). Perfusate lactate concentration decreased from baseline until the end of perfusion (10.38 ± 0.76 mmol/L vs 1.22 ± 0.26 mmol/L; P < 0.001). Posttransplantation, animals transplanted with NEVKP versus SCS grafts demonstrated similar serum creatinine peak levels (NEVKP, 2.0 ± 0.5 vs SCS 2.7 ± 0.7 mg/dL; P = 0.11) and creatinine clearance on day 10 (NEVKP, 65.9 ± 18.8 mL/min vs SCS 61.2 ± 15.6 mL/min; P = 0.74). After 10 days of follow-up, animals transplanted with NEVKP grafts had serum creatinine and blood urea nitrogen values comparable to their basal levels ( P = 0.49 and P = 0.59), whereas animals transplanted with SCS grafts had persistently elevated serum creatinine and blood urea nitrogen when compared with basal levels ( P = 0.01 and P = 0.03). Conclusions: Continuous pressure-controlled NEVKP is feasible and safe in good quality heart-beating donor kidney grafts. It maintains a physiologic environment and excellent graft function ex vivo during preservation without causing graft injury. Abstract : The authors compare the role of ex situ normothermic machine perfusion of 8 hours versus static cold storage in a porcine autotransplantation model. It suggests that continuous pressure-controlled normothermic ex vivo kidney perfusion is feasible and safe in good quality heart-beating donor kidney grafts.